Aspergillus oryzae와 Bacillus subtilis를 순차접종 발효한 갈색거저리유충과 누에번데기 발효물의 품질특성 - 강상훈(Sanghun Kang); 정장호(Chang-Ho Chung) (한국식품과학회지, 2022)
Defatted soybean, larvae of brown mealworm (Tenebrio molitor), and powdered pupae of silkworm (Bombyx mori) were fermented in solid and liquid forms using Aspergillus oryzae and Bacillus subtilis. The protein degradation rate (NDR) through solid fermentation was the highest in the fermented soybean control sample (54.69±6.54%), followed by silkworm pupae (34.82±5.99%) and brown mealworm larvae (30.54±3.80%). When these edible insects were fermented in liquid form, solid extraction yield was 37.73-46.88%, and protein yield was 47.47-63.02%. NDR of fermented liquid form products increased to 58.90, 52.62, and 50.13% for soybean, brown mealworm larvae, and silkworm pupae, respectively. SDS-PAGE of the liquid fermented products confirmed that microbial fermentation decomposed higher-molecular-weight proteins into small polypeptides. In vitro digestibility of liquid forms of edible insects increased by 1.26 to 1.53 times after fermentation. The protein solubility, foaming ability, and foam stability of liquid-fermented edible insects all tended to increase through fermentation. 탈지 갈색거저리 유충과 번데기 분말을 A. oryzae 및 B. subtilis 균주를 이용하여 발효추출물을 제조하였다. 그 결과 발효추출물의 단백질 함량은 69.67-86.06% (p<0.001)이며, 액상발효물의 고형분 수율은 37.76-46.88% (p<0.001)로 나타났다. 단백질 분해율은 대두발효물(esS) 58.90%, 갈색거저리유충(esT; 52.62%), 누에번데기(esP; 50.13%) 순으로 나타났으며(p<0.001), 단백질 수율의 경우 47.47-63.02% 이였다(p<0.001). 또한 SDS-PAGE 결과, 발효과정을 거치지 않은 각각의 탈지원물과 비교 시 액상발효물들의 단백질이 저분자로 분해됨을 확인하였다. 액상발효물의 in vitro 소화율을 측정한 결과, 탈지원물(59.60-76.03%)에 비해 발효추출물의 단백질 소화율이 91.02-95.86%로 1.26-1.53배 증가하였다(p<0.001). 액상발효물의 단백질 용해도, 거품형성능, 거품안정성 모두 발효과정을 통해 수치가 증가하는 경향성을 나타났다. 이를 바탕으로 발효공정을 통한 단백질 추출물 공정의 가능성을 확인하였으며, 추후 추출물의 이화학적 특성 및 기능성을 기반으로 새로운 기능성 식품 소재 개발에 기여할 수 있을 것으로 보인다.